Teaching Narrative
XV, 214 p.
Keywords: Narrative is everywhere and has unique powers: to enchant and inspire, to make sense of our lives and ourselves and to afford us an enriched understanding of alternative worlds and lives and of better futures – though narrative also has the potential to coerce and oppress. Narrative is at the centre at all stages of the English curriculum and has been the subject of a burgeoning critical industry. This timely volume addresses the many ways in which recent thinking has informed the teaching of narrative in university classrooms in the UK and the USA. Distinguished teachers from both countries range widely across narrative topics and genres, including the opportunities opened up by new technologies, and chapters articulate students’ own individual and collaborative experiences in the teaching/learning process. The result is a volume that explores the pleasurable challenges of working with students to help them appreciate and assess the power that narrative exerts, to become reflectivecritics of its inner workings as well as exponents of narrative themselves. .